Inclusive human development in sub-Saharan Africa - Simplice Asongu; Joseph Nnanna (African Governance and Development Institute (AGDI), 2020)
This study assesses the role of income levels (low and middle) in modulating governance (political and economic) to influence inclusive human development. The empirical evidence is based on interactive quantile regressions and forty-nine countries in sub-Saharan Africa for the period 2000-2002.The following main findings are established. First, low income modulates governance (economic and political) to positively affect inclusive human development exclusively in countries with above-median levels of inclusive human development. It follows that countries with averagely higher levels of inclusive human development are more likely to benefit from the relevance of income levels in influencing governance for inclusive development. Second, the importance of middle income in modulating political governance to positively affect inclusive human is apparent exclusively in the median while the relevance of middle income in moderating economic governance to positively influence inclusive human development is significantly apparent in the 10th and 75th quantiles. Third, regardless of panels, income levels modulate economic governance to affect inclusive human development at a higher magnitude, compared to political governance. Policy implications are discussed in the light of the post-2015 agenda of sustainable development goals and contemporary development paradigms. This study complements the extant sparse literature on the inclusive human development in Africa.
Keywords: D31; I10; I32; K40; O55; 330; Sustainable development; Income levels; Governance; Sub-Saharan Africa